Actualización - Estudio Hidráulico del Río San Eugenio, Determinación de Zonas de Amenaza por Inundación. Santa Rosa De Cabal, Risaralda. (2023)
This study is presented to elucidate the hydraulic behavior of the San Eugenio River in Santa Rosa de Cabal (Risaralda), using hydrological information from IDEAM - CARDER to incorporate it into the two-dimensional software IBER 3.3.1, and in this way calculate the floodable areas with information from water levels and velocities for return periods of 100 and 500 years. The results obtained allowed us to define the areas under threat of flooding, with the most affected sectors being those neighborhoods located in the floodplain (occupied with human settlements or socioeconomic activities) where the water height exceeds 1 meter in depth.